Comparative Metabolomics and Proteomics Reveal Vibrio parahaemolyticus Targets Hypoxia-Related Signaling Pathways of Takifugu obscurus - Xu, Jiachang; Yu, Xue; Ye, Hangyu; Gao, Songze; Deng, Niuniu; Lu, Yuyou; Lin, Haoran; Zhang, Yong; Lu, Danqi (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) raises the issue of how hypoxia destroys normal physiological function and host immunity against pathogens. However, there are few or no comprehensive omics studies on this effect. From an evolutionary perspective, animals living in complex and changeable marine environments might develop signaling pathways to address bacterial threats under hypoxia. In this study, the ancient genomic model animal Takifugu obscurus and widespread Vibrio parahaemolyticus were utilized to study the effect. T. obscurus was challenged by V. parahaemolyticus or (and) exposed to hypoxia. The effects of hypoxia and infection were identified, and a theoretical model of the host critical signaling pathway in response to hypoxia and infection was defined by methods of comparative metabolomics and proteomics on the entire liver. The changing trends of some differential metabolites and proteins under hypoxia, infection or double stressors were consistent. The model includes transforming growth factor-β1 (TGF-β1), hypoxia-inducible factor-1α (HIF-1α), and epidermal growth factor (EGF) signaling pathways, and the consistent changing trends indicated that the host liver tended toward cell proliferation. Hypoxia and infection caused tissue damage and fibrosis in the portal area of the liver, which may be related to TGF-β1 signal transduction. We propose that LRG (leucine-rich alpha-2-glycoprotein) is widely involved in the transition of the TGF-β1/Smad signaling pathway in response to hypoxia and pathogenic infection in vertebrates as a conserved molecule.